Sejarah Pondok Pesantren Salafiyah Tarbiyah Islamiyah Koto Kandis (1950-2017) - Widya Elfami Putri; Rusdi Rusdi (Jurusan Sejarah FIS UNP, 2019)
This study describe the History of Pondok Pesantren Salafiyah Tarbiyah Islamiyah Koto Kandis (1950-2017). This research uses the historical method of the process: Heuristics, or data collection, then continued the procces of source criticism and interpretation of data, the final stage is the writing of history so that’s way this research can be completed. The results showed that the first founders of “Sekolah Tarbiyah” (Pondok Pesantren Salafiyah Tarbiyah Islamiyah Koto Kandis) are Pakia Nantang (1910-1969) and “niniak mamak” of Koto Kandis, also helped by Koto Kandis’s society due to concerns about childrens who less getting education of religion and economics factors, the society of Koto Kandis was so poor. Then helped by H. Timu (1927-1987), Buya Abdul Mu’is (1930-1993) Buya Abu Sidar Kalimandaro (born 1930th), and Buya Kamaruddin (born 1932th) to teach some education of religion like “Kitab Gundul” and others. On 2006th “Sekolah Tarbiyah” has changed to be “Pondok Pesantren Salafiyah Tarbiyah Islamiyah Koto Kandis.”